Reverberatory Furnaces in the Puna of Jujuy, Argentina, during colonial times (final XVI to beginning of XIXth centuries): Between Europe and America - Angiorama, Carlos Ignacio (2013)
The Puna of Jujuy, Argentina, is part of the southern extreme of the Andes High Plateau. In this region there are mineral resources, such as gold and silver, which became a great attraction for the European conquerors during colonial times. This paper focuses on the study of the extractive metallurgical technology that was employed in four mining-metallurgical sites in this region dedicated to silver exploitation. In these sites, we have registered the presence of reverberatory furnaces, a technology that was probably brought to America from Europe and experienced certain changes and innovations in the different places where it was applied for smelting and refining silver or copper minerals. To date, the function and characteristics of this kind of furnaces in the Andes are not well known because there are only few registered and published. The excellent conservation of most of the furnaces found in the sites we are presenting makes them a great source of information for the study of the colonial metallurgy in this region, where the mining and metallurgical activities had a major importance for the Spanish population. Moreover, travellers and chroniclers only wrote about colonial exploitation in the great mining centres with no reference to marginal areas such as the Puna of Jujuy. In that sense, our presentation aims to show the results of the detailed study of these furnaces, its functions and performance, based on our fieldwork and the results of archaeo-metric analyses on samples of smelting slag and vitrified clay.